COVID-19 in India: Weighing Schools Reopening Amid Black Clouds of Third Wave Hovering Around - Gupta, Vikas; Singh, Abhishek (Journal of Pharmacy Practice and Community Medicine)
The Coronavirus disease (COVID-19) wreaked havoc across the globe with the onset of year 2020, which posed an extra ordinary situation in front of mankind. The black clouds of third wave are still hovering around us.